Ocorrência de candidíase bucal em pacientes com câncer na região de cabeça e pescoço - Florentino, Ana Carolina Andrade (2016)
Introduction: Oral candidiasis is a common fungal infection in patients irradiated in the head and neck region. In antineoplastic treatment period they undergo a transient immunosuppression framework in which there is a predisposition to the proliferation of opportunistic fungi. In the oral cavity clinical forms of candidiasis may be associated with mucosal changes, manifesting in acute pseudomembranous forms, acute atrophic, chronic hyperplastic, chronic atrophic, glossitis rhomboid and angular cheilitis. The fungal infection provides the oral cavity, oropharynx and hypopharynx symptoms of burning, which difficult, reducing the quality of life of the patient, as well as hamper the antineoplastic treatment. Thus, effective treatments are important, to avoid these complications. Objectives: To investigate the occurrence of oral candidiasis diagnosed in patients with head and neck cancer treated at the dental clinic from January 2013 to June 2014; evaluate the antifungal therapy and predisposing factors related to oral candidiasis; relate time of treatment, clinical course of candidiasis and symptoms; relate anatomical site of the tumor, presence of candidiasis, radiation time and / or chemotherapy and stage of cancer. Material and Methods: A retrospective, descriptive, cross-sectional, chart analysis from the “Aplicativo de Gestão para Hospitais Universitários” (AGHU) (Management Application for University Hospitals) and Hospital files of the Clinical Cancer Hospital, Federal University of Uberlândia. Results: Of the total assessed medical records (83 patients), 48 patients (57.8%) had at least one episode of oral candidiasis. The antifungal agents used were nystatin, miconazole and fluconazole oral gel for up to three months. The most frequent symptoms were dry mouth (p = 0.006) and dysgeusia (p = 0.031). Antifungal therapies have been effective in 95.8% of patients. Chemotherapy in this study had statistically significant (p = 0.021) in involvement by oral candidiasis, but it was not possible to evaluate the periods between chemotherapy, and 26.5% of patients had the first fungal infection with cumulative dose 1800 cGy radiotherapy. Conclusion: The majority of patients experienced at least one episode of oral candidiasis during antineoplastic treatment. The appearance of oral candidiasis was related to the following items: the cumulative dose of radiotherapy, tumor hyposalivation and anatomical sites. The most patients evolved to cure after antifungal treatment. Symptoms most frequently reported were burning, odynophagia, trismus, xerostomia, dysphagia, and dysgeusia. Most of the patients were affected by oral candidiasis in a cumulative dose of 1800 cGy radiotherapy.